EXCHANGE RATE DEVALUATION, INTERNATIONAL TRADE AND ECONOMIC MISERY IN NIGERIA: IS THERE A MODERATING EFFECT? - OKUNGBOWA, EWERE FLORENCE; OSARO, VICTORY ESEOSA; EBURAJOLO, COURAGE OSE (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The study examines the effects of exchange rate and international trade on the economic Misery in Nigeria for the period of 1986 to 2023 using the Dynamic Ordinary Least Square (DOLS) technique. The findings revealed significant relationships between all the variables and economic conditions, offering insights crucial for policy formulation and economic management. The analysis demonstrates that exchange rate devaluation plays a pivotal role in shaping economic misery in Nigeria, export trade was found to have a positive and significant impact on economic misery based on the negative coefficient which implies that higher import results to a decline in economic misery. Imports show a significant positive impact on economic misery, suggesting that higher levels of imported goods contribute to economic challenges in form of inflation in Nigeria. The interaction between exchange rate devaluation and export trade also revealed significant impacts on economic misery. This interaction indicates that while export growth can alleviate economic distress, the extent of this benefit depends on exchange rate dynamics as increased exchange rate depreciation was seen to have dampening effect on export trade as their interaction tend to worsen economic misery in Nigeria. Consequently, this study reveals nuanced dynamics, and emphasized the need for coordinated policy measures to optimize export competitiveness amidst exchange rate fluctuations. Proactive policy interventions that promote export diversification, enhance production capacities, and manage import dependencies are essential for fostering sustainable economic growth and reducing economic misery in Nigeria.